Tetrameric Lanthanide‐Substituted Silicotungstate Ln8Si4W40 Nanoclusters: Synthesis, Structural Characterization, Electrochemistry, and Catalytic Application for Oxidation of Thioethers. Issue 11 (5th March 2021) - Khan, Imran; Das, Vivek; Teillout, Anne‐Lucie; Mbomekallé, Israël‐Martyr; de Oliveira, Pedro; Sahoo, Subash Chandra; Hussain, Firasat
Abstract: All the title nanoclusters 1 –10 with the molecular formula [(Ln2 SiW10 O38 )4 (W3 O8 )(OH)4 (H2 O)2 ] 26− [Ln III =Sm (1 ), Eu (2 ), Gd (3 ), Tb (4 ), Dy (5 ), Ho (6 ), Er (7 ), Tm (8 ), Yb (9 ), and Y (10 )] have been synthesized and isolated as mixed sodium and potassium salts. These nanoclusters are characterized by various analytical techniques such as FT‐IR, UV/Vis, Photoluminescence, Single crystal X‐ray diffraction, Electrochemistry, ICP‐AES and Thermogravimetric analysis, and Powder X‐ray diffraction. The Ln8 Si4 W40 complexes show high efficiency and selectivity for the oxidation of thioethers using H2 O2 as green oxidant. It is worth mentioning that the catalyst can be recovered even after five cycles of reaction with only a slight loss in its activity. Abstract : A series of ten lanthanide‐substituted Ln8 Si4 W40 nanoclusters have been synthesized possessing a potential application in the field of catalysis for the oxidation of thioethers. The complexes were characterized by various analytical techniques. Due to the redox properties of polyoxometalates, the electrochemistry of the synthesized nanoclusters were studied. Furthermore, the photoluminescence properties were investigated in three complexes.